2010
DOI: 10.2215/cjn.01090210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Cognitive Impairment in Hemodialysis Patients

Abstract: Background and objectives: Cognitive impairment is common among persons with ESRD, but the underlying mechanisms are unknown. This study evaluated the prevalence of cognitive impairment and association with modifiable ESRD-and dialysis-associated factors in a large group of hemodialysis patients.Design, setting, participants, & measurements: Cross-sectional analyses were conducted on baseline data collected from 383 subjects participating in the Frequent Hemodialysis Network trials. Global cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
156
5
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 30 publications
9
156
5
8
Order By: Relevance
“…These include a potential for survival bias that may have resulted in an underestimation of the burden of disability, inability to generalize across all populations, and a lack of longitudinal outcome data. Several studies have noted that patients on dialysis (both HD and PD) have a high burden of cognitive impairment (34,37,38). Through our choice chair without the use of their arms or an aid, while 51% were unable to perform the TUG mobility test within the normal range of 0-10 s.…”
Section: Study Populationmentioning
confidence: 94%
“…These include a potential for survival bias that may have resulted in an underestimation of the burden of disability, inability to generalize across all populations, and a lack of longitudinal outcome data. Several studies have noted that patients on dialysis (both HD and PD) have a high burden of cognitive impairment (34,37,38). Through our choice chair without the use of their arms or an aid, while 51% were unable to perform the TUG mobility test within the normal range of 0-10 s.…”
Section: Study Populationmentioning
confidence: 94%
“…Our results confirm prior studies that have demonstrated a high prevalence of cognitive impairment in this population. 3,[20][21][22] In one study, the MMSE was administered to 336 dialysis patients: 22% of subjects had mild impairment (MMSE scores 18-23) and 8% had moderate-severe impairment (MMSE scores 0-17). 3 In another study evaluating 338 hemodialysis patients, 14% were classified with mild impairment, 36% with moderate impairment, 37% with severe impairment, and 13% with normal cognition.…”
mentioning
confidence: 99%
“…22 In the Frequent Hemodialysis Network, impaired executive function, defined by failure to complete the Trail Making B task within 5 minutes, was common among hemodialysis patients but was not strongly associated with patient or dialysis-associated factors. 21 Our study substantially adds to these by performing detailed cognitive testing, focusing on both memory and executive function, evaluating a wide range of risk factors for each form of cognitive impairment, and comparing the results to validated normative data. We also demonstrate that, even among those with MMSE score $24, there is a high frequency of more subtle degrees of cognitive impairment.…”
mentioning
confidence: 99%
“…An association between renal failure and cognitive impairment has been reported (14)(15)(16). The point prevalence of cognitive impairment and dementia was two-fold higher in patients with ESRD than in those without ESRD (17).…”
Section: Cognitive Impairmentmentioning
confidence: 96%